Meningkatkan Keputusan Pembelian Kosmetik dengan Advertising dan Online Customer Reviews - Indryasari, Ni Made Nesa Diana; Wimba, I Gusti Ayu; Susanti, Putu Herny (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The e-commerce business in Indonesia is developing very rapidly, so it has a big impact on business changes. This study was conducted to test the effect of advertising and online customer reviews on the purchasing decisions of Wardah cosmetic products. The population is consumers who have bought Wardah cosmetics on the Shopee marketplace in Denpasar City, the number of which is not known with certainty. The sampling technique used was purposive sampling and accidental sampling (convenience sampling) with a sample of 91 respondents. The next data will be analyzed using multiple linear regression method. The results obtained are partially and simultaneously, advertising and online customer reviews have a positive and significant effect on purchasing decisions for Wardah cosmetic products. Suggestions in research so that advertisements are even more attractive, always maintain product quality and provide training to resellers.